The whole difference : selected writings of Hugo von Hofmannsthal - Hofmannsthal, Hugo von, 1874-1929 (Princeton University Press, 2008)
Hugo von Hofmannsthal is one of the modern era's most important writers, but his fame as Richard Strauss's pioneering collaborator on such operas as Der Rosenkavalier and Die Frau ohne Schatten has obscured his other remarkable writings: his precocious lyric poetry, inventive short fiction, keen essays, and visionary plays. The Whole Difference, which includes new translations as well as classic ones long out of print, is a fresh introduction to the enormous range of this extraordinary artist, and the most comprehensive collection of Hofmannsthal's writings in English. Selected and edited by t.